EFFECT OF ADS AND QUALITY OF PRODUCTS IN DECISION OF PURCHASING FRISIAN FLAG PRODUCT IN MEDAN CITY - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The company must be aware that in the era of globalization, advertising and product quality is an important factor to achieve success. Where advertising and product quality can affect consumer to buy goods and services companies at the time they need.